CD40-deficient mice generated by recombination-activating gene-2-deficient blastocyst complementation. - Castigli, E (1994)
To study the role of B-cell antigen CD40 in immune responses, mouse embryonic stem (ES) cells in which both copies of the gene encoding CD40 had been disrupted by homologous recombination were injected in RAG-2 (recombination-activating gene-2)-deficient blastocysts to generate chimeras in which all mature lymphocytes are derived from the CD40-deficient ES cells. T- and B-cell number and phenotype were normal in the CD40-/- chimeras. However, B cells failed to proliferate and undergo isotype switching in vitro in response to soluble CD40 ligand (sCD40L) with interleukin 4 (IL-4) but responded normally to lipopolysaccharide (LPS) with IL-4. CD40-/- chimeras completely failed to mount an antigen-specific antibody response or to develop germinal centers following immunization with the T cell-dependent (TD) antigen keyhole limpet hemocyanin. In contrast, CD40-/- mutant mice responded normally to the T cell-independent (TI) antigens, 2,4,6-trinitrophenyl (TNP)-LPS and TNP-Ficoll. The most noticeable alteration in the serum immunoglobulin levels of young (6-8 weeks old) CD40-/- animals was absence of IgE and severe decrease of IgG1 and IgG2a. These results confirm the essential role of CD40- CD40L interactions in the antibody response to TD antigens and in isotype switching.